The impact of severe hypoglycemia on renal impairment in type 2 diabetes. Issue 3 (June 2015) - Lee, Yu-Li; Chen, Brian K.; Lin, Kun-Der; Su, Rong-Wei; Lee, Mei-Yueh; Hsiao, Pi-Jung; Shin, Shyi-Jang
Highlights: Severe hypoglycemia (SH) is a risk for Cr increase and eGFR decrease in T2DM. High basal Cr and low eGFR predict the aggravation of renal dysfunction in SH. Old T2DM with DKD are vulnerable to aggravation of renal dysfunction by SH. Abstract: Aims: Hypoglycemia has been reported to be associated with the development of microvascular events. Therefore, it is important to assess the impact of severe hypoglycemia on renal dysfunction in type 2 diabetes. Methods: We conducted a retrospective cohort study in a large tertiary care hospital from 2004 to 2013. A total of 101 patients with type 2 diabetes from the outpatient department with a history of severe hypoglycemia were studied. A random sample of 101 patients with type 2 diabetes without any hypoglycemia was selected by matching values of baseline blood creatinine, age, sex and diabetic duration. Results: Baseline blood creatinine (1.42 ± 0.75 mg/dL) significantly increased to 1.77 ± 1.26 and 1.93 ± 1.54 mg/dL, and baseline eGFR (44.37 ± 26.13 ml/min/1.73 m 2 ) decreased to 41.28 ± 27.70 and 37.64 ± 24.54 ml/min/1.73 m 2 at the onset of hypoglycemia and the follow-up visit in severe hypoglycemia group; while no significant changes were observed in the group without any hypoglycemia. Multiple linear regression analysis showed that severe hypoglycemia is an independent risk factor for increase in blood creatinine and decrease in eGFR in all patients with type 2 diabetes, and that baseline creatinine, longer diabetic duration and lower HbA1c are risk factors for the deterioration of renal impairment in the group with severe hypoglycemia. Conclusion: Our results showed that severe hypoglycemia is associated with deterioration of renal function in type 2 diabetes with chronic kidney disease and the patients with higher baseline creatinine and a longer diabetic duration could be more vulnerable to aggravation of renal function impairment.